ANALISIS RISIKO PRODUKSI STROBERI DENGAN METODE Z-SCORE DAN VALUE AT RISK PADA CV. BUMI AGRO TECHNOLOGY, JAWA BARAT - Astri Indira; Lucyana Trimo (Universitas Galuh Ciamis, 2021)
CV. Bumi Agro Technology is one of the strawberry farming in West Java which is still surviving until now amidst various constraints on strawberry fruit production, such as fluctuating production yields and production failures. This indicates that there is a risk that occurs in strawberry production activities. The research objectives are (1) identifying the causes of risk, (2) determine the probability and impact of risk, and (3) proposing various risk management strategies. The research design used a qualitative design with a case study research technique. The analytical tools used are Z-Score analysis and Value at Risk analysis. The results showed that the risk of production was caused by various sources of risk, namely human resources with a probability of 38.2% and an impact of Rp. 2,018,298, capital or farm finance with a probability of 30.5% and an impact of Rp. 1,015,439, plant pests and diseases with a probability of 24.5% and an impact of Rp. 1,097,284, and natural resources with a probability of 10.7% and an impact of Rp. 738,319. Based on the results of risk measurement analysis, a strategy can be formulated that can be implemented to minimize risk. The source of risk that causes the highest production risk is human resources. One of the proposed strategies that can be implemented to reduce the risk of production caused by human resources is empowering human resources who have low educational background and insight by improving the quality of education for the labor through counseling and training accompanied by field coordinators or field extension officers and then immediately implemented in the field.